Educating Alice : adventures of a curious woman - Steinbach, Alice (New York : Random House, 2004)
Steinbach, a Pulitzer Prize-winning journalist, shares details of her studies, anecdotes, and lessons learned after leaving her job at the Baltimore Sun to travel around the world.
Keywords: Steinbach, Alice; Steinbach, Alice -- Travel; Journalists -- United States -- Biography